Causal relationship between hormone levels and lung cancer: a Mendelian randomization study - Zhiying Feng; Jingmin Fu; Kangyu Wang; Jiaxin Yang; Xuelian Jiang; Qiong Wu (Frontiers in Endocrinology)
BackgroundLung cancer is a highly prevalent neoplastic disease in various regions of the world, but the mechanism of its occurrence, development, and metastasis is not clear. Different hormone levels have different potential roles in the occurrence, development, and metastasis of lung cancer, but the association between hormone levels and lung cancer is not clear.ObjectiveThis study aims to explore the causal relationship between hormone levels and lung cancer using Mendelian randomization. Sensitivity and heterogeneity tests were conducted to ensure the reliability of the results, offering insights into the prevention, diagnosis, and treatment of lung cancer.MethodsWe employed a two-sample Mendelian randomization (MR) analysis using large-scale publicly available genome-wide association studies (GWAS) data to assess the causal relationship between hormone levels and lung cancer. We explored the causal relationship between 15 hormones and three subtypes of lung cancer. The inverse variance weighted (IVW) method was used as the primary analysis, while MR-Egger, weighted median, weighted mode, and simple median were applied as supplementary methods. Sensitivity and heterogeneity tests were conducted to ensure the robustness of the findings.ResultsWe identified six hormone levels to be significantly associated with lung squamous cell carcinoma (LUSC): total testosterone, oestradiol, thyrotropin-releasing hormone, insulin, parathyroid hormone, and glucocorticoid. Among them, total testosterone, estradiol, and thyrotropin-releasing hormone were negatively correlated with morbidity. Insulin, prolactin levels, and parathyroid hormone were positively correlated with morbidity. Five hormone levels were significantly associated with lung adenocarcinoma (LUAD): luteinizing hormone, thyroid hormones, insulin, prolactin levels, and parathyroid hormone. Luteinizing hormone and thyroid hormones were negatively correlated with morbidity, while insulin, prolactin levels, and parathyroid hormone were positively correlated with morbidity. Similarly, five hormone levels were linked to small cell lung cancer (SCLC): total testosterone, luteinizing hormone, estradiol, PTHrP, and insulin. Total testosterone and luteinizing hormone were negatively correlated with morbidity, while estradiol, Parathyroid Hormone-Related Peptide (PTHrP), and insulin were positively correlated with morbidity. Several hormones were associated with different subtypes of lung cancer. Insulin was significantly associated with all three types of lung cancer. Testosterone showed positive effects in LUSC and SCLC, and estradiol had varying effects, with a negative correlation in SCLC and a positive correlation in LUSC. Testosterone and estradiol were not significantly associated with LUAD. Luteinizing hormone showed positive effects in LUAD and SCLC, and parathyroid hormone showed negative effects in LUSC and LUAD.ConclusionThis study demonstrates significant causal relationships between specific hormone levels and various types of lung cancer, providing valuable insights for prevention, diagnosis, and treatment strategies of lung cancer.